Penerapan Metode End Of File Pada Steganografi Citra Gambar dengan Memanfaatkan Algoritma Affine Cipher sebagai Keamanan Pesan - Fauzi, Achmad; Rahayu, Rizka Putri (MEANS (Media Informasi Analisa dan Sistem), 2018)
The development of the world of information technology is very fast lately influential in all aspects of life. Kriprografi is a science based on mathematical techniques to deal with information security such as confidentiality, data integrity, and entity authentication. Affine Cipher or Affine password is a substitution cipher that is specifically for encryption or decryption per character. Therefore, Affine's password includes the stream cipher cryptographic algorithm. Steganography is a way of hiding the contents of a data in a cover of media or other digital data that cannot be predicted by ordinary people so as not to arouse suspicion from those who see it. The steganography image file has the same number of pixels as the original image file and there is no color difference between the two. The size of the steganography image file will increase, according to the length of the hidden message plus 6 bytes, in the form of 1 byte EOF and 5 byte message length. The End Of File (EOF) method is a technique for inserting data at the end of a file. When opened with a photo editor application, both images have the same pixel size, namely 240 x 238, and do not change color. In this test, what changes is the size of the image file, ie the initial size of the image is 49.132 bytes, changes to 49.145 bytes, or there is an addition of 13 bytes